218 Evaluating the Relationship Among Erectile Dysfunction, Prostate Cancer Treatment Type and Inflatable Penile Prosthesis (IPP) Implantation. Issue 1 (1st April 2022) - Shah, T; Shen, C; Jain, K; Schasefer, E; Zhou, S; Fried, D; Helmer, D; Sadeghi-Nejad, H
ABSTRACT: Introduction: Sexual health problems affect approximately 60% of male cancer survivors in the U.S. Erectile dysfunction (ED) is the most common sexual health condition men seek professional help for after cancer treatment with some studies reporting ED rates as high as 85% in these men. Inflatable penile prosthesis (IPP) implantation is a safe and highly effective form of ED treatment for patients who fail or cannot tolerate medical therapies. A 2011 study suggested that IPPs are under-utilized by urologists, as less than 1% of men with prostate cancer and ED received IPP following radical prostatectomy or external beam radiation. Objective: To better characterize the utilization of IPP treatment, we examined the relationships between ED, prostate cancer treatment type and IPP implantation in a national cohort. Methods: We performed a retrospective review of older SEER-Medicare patients who were diagnosed with local/regional prostate cancer between 2006 and 2011 and treated with surgery or radiation for it, with and without ED. Using ICD9/CPT/HCPCS codes we created a cohort of patients who has receipt of surgery or radiation within 3 months of cancer diagnosis as well as diagnosed ED within 5-years after undergoing treatment. Chi-square/Wilcoxon tests were used to detect significant differences between the surgical and radiation treatment groups for ED rates and use of IPP among those with ED. Results: Of the 31, 854 patients in our cohort, 10, 475 (32.9%) received surgery and 21, 152 (66.4%) received radiation only. Overall, ED was significantly more common for surgical (65.2%) than for radiation patients (33.8%, p<.001). For the subset of 14, 121 patients with ED (overall IPP use=2.5%), IPP implantation was significantly more frequent for surgical patients (n=6, 976, IPP use= 3.6%) than for radiation patients (n=7, 145, IPP use=1.4%, p<.001). Conclusions: Shockingly few (2.5%) prostate cancer patients with ED received IPP, with only 1.4% of radiation patients undergoing IPP vs. 3.6% of RALP patients. IPP under-utilization may be due to greater clinical focus on cancer treatment rather than quality-of-life issues. Discrepancies in ED rates between radiation and surgery may also be partially explained by lack of follow-up standardization and highly variable sexual dysfunction reporting, especially in the radiation literature. These findings highlight the importance of thorough counseling about all treatment options including penile prosthesis surgery for prostate cancer patients with ED. Disclosure: No